KINESIC COMMUNICATION COMPONENTS OF NON-VERBAL COMMUNICATION OF SERIAL KILLERS IN AMERICAN ARTISTIC DISCOURSE OF 20 th CENTURY - Nytspol, V. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article investigates the non-verbal behavior of serial killers, in particular its kinetic communicative components. The study was based on American Thriller novels of the 20th century. The following kinemes, such as a smile, a gaze, a gesture, as well as facial expression are analyzed. The combination of the kinesic component with other nonverbal elements, as well as its interaction with verbal means of expressing thought, is considered.